Molecular beacons with JOE dye: Influence of linker and 3′ couple quencher. Issue 5 (October 2016) - Tsybulsky, Dmitry A.; Kvach, Maksim V.; Ryazantsev, Dmitry Y.; Aparin, Ilya O.; Stakheev, Alexander A.; Prokhorenko, Igor A.; Martynenko, Yury V.; Gontarev, Sergey V.; Formanovsky, Andrey A.; Zatsepin, Timofei S.; Shmanai, Vadim V.; Korshun, Vladimir A.; et al.
Abstract: Molecular beacons carrying JOE dye (4′, 5′-dichloro-2′, 7′-dimethoxy-6-carboxyfluorescein) on a rigid or flexible linker and one or two BHQ1 quenchers have been prepared and tested in real-time PCR using Fusarium avenaceum elongation factor 1α DNA template. The probes were different in their structures (loop size and stem length), linkers for dye attachment (6-aminohexanol or trans -4-aminocyclohexanol), quencher composition (single and double BHQ1) to elucidate the influence of all these features. Fluorogenic properties of the probes were studied and compared to those of FAM (fluorescein)-based probes. All the factors – stem length, JOE vs FAM, rigid vs flexible linker, single vs double quencher – appeared to play a considerable role in the probe's fluorescent properties and determine the usability of the probe at two different temperatures of fluorescence detection (55°С and 64°С). Highlights: A series of Molecular beacons with different structure carried JOE was tested in qPCR. JOE proved to be brighter than FAM with probes with the same sequence. The length of MB's stem was varied from 4 to 8 bp to optimize MBs design. A rigid linker for JOE attaching is preferable for increasing light-up of fluorescence. The second BHQ1 in probe significantly decrease background of fluorescence.